The US liberal political and academic establishment on national-territorial transformation of Russia in 1917–1922 - V. V. Romanov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines the evolution of approaches and assessments of the US political and academic establishment regarding the national-territorial transformation of Russia at the final stage of the First World War, during the Revolution and the Civil War. During that period the US diplomacy was focused on developing and implementing its own ambitious program for the liberal-democratic reorganization of the post-war world with particular focus on issues of national self-determination. As a result, Wilson’s administration could not remain indifferent to the dramatic changes on the territory of the former Russian Empire. However, as the author notes, for European politicians its responses appeared rather unusual and often puzzling. The latter was due to a very specific interpretation of the principle of national self-determination adopted by W. Wilson and his associates as the right of the civil society to self-government rather than the right to ethnic separation. At the same time, the right to independently determine their own destiny was reserved, in a spirit of social-Darwinism, only for peoples who had reached a certain maturity. And moreover, each particular case was additionally assessed in terms of both political rationality and developments of political situation in Russia in general. For instance, the US liberal political and academic establishment consistently supported the independence of Poland and Finland while most other national minorities (the peoples of the Baltic region, Ukrainians, Belarusians, Armenians, Georgians, Azerbaijanis, the peoples of Central Asia, etc.) were usually encouraged to defend their autonomy within a united and democratic Russia. The author notes, that the US policy towards Russia became particularly controversial after the Bolsheviks came to power: the consistent rejection of the Bolshevik reforms was accompanied by the reluctance to incite separatism on the national outskirts out of fear of Russia’s uncontrolled disintegration and its subsequent transformation into a site of endless ethnic conflicts. As a result, the United States did not recognize most of the national entities that declared their independence in 1917–1922. At the same time, the author concludes that the growing ideological and political confrontation with Soviet Russia in the following years did not allow the US leaders to adequately assess the national-territorial transformations that were brought about by the creation of the USSR.